2016
DOI: 10.1007/s10763-016-9723-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Critical Thinking in Physics: Development and Validation of a Critical Thinking Test in Electricity and Magnetism

Abstract: Although the development of critical thinking (CT) is a major goal of science education, adequate emphasis has not been given to the measurement of CT skills in specific science domains such as physics. Recognizing that adequately assessing CT implies the assessment of both domain-specific and domain-general CT skills, this study reports on the development and validation of a test designed to measure students' acquisition of CT skills in electricity and magnetism (CTEM). The CTEM items were designed to mirror … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(153 citation statements)
references
References 30 publications
2
133
0
18
Order By: Relevance
“…However, Ennis (1989) found that critical thinking has subject specificity (similar to domain specificity); therefore, evaluation scales for critical thinking abilities vary among different fields and require different design considerations to develop more proper educational or evaluation tools (Tiruneh, Cock, Weldeslassie, Elen, & Janssen, 2016). A study of Renaud and Murray (2008) using psychology as the learning content showed results consistent with Ennis' opinion.…”
Section: Introductionmentioning
confidence: 81%
“…However, Ennis (1989) found that critical thinking has subject specificity (similar to domain specificity); therefore, evaluation scales for critical thinking abilities vary among different fields and require different design considerations to develop more proper educational or evaluation tools (Tiruneh, Cock, Weldeslassie, Elen, & Janssen, 2016). A study of Renaud and Murray (2008) using psychology as the learning content showed results consistent with Ennis' opinion.…”
Section: Introductionmentioning
confidence: 81%
“…However, the experience of evaluating Immersion-and Infusion-based CT interventions for the acquisition of domain-specific CT skills has not been well valued. A few researchers developed and validated CT tests based on content from specific subject-matter domains: the Psychological CT Assessment in the domain of psychology (Lawson, 1999), the Biological CT exam (McMurray, 1991) and the Critical Thinking in Electricity and Magnetism test in the domain of physics (CTEM; Tiruneh, De Cock, Weldeslassie, Elen, & Janssen, 2017). The empirical evidence on whether performance in a domain-specific CT test relates to performance in one of the abovementioned domain-general CT tests has been scant.…”
Section: The Assessment Of Ct Outcomesmentioning
confidence: 99%
“…CTEM (Tiruneh et al, 2017) The CTEM was administered to measure domainspecific CT proficiency in line with the desired domain-specific CT outcomes described in Table 2. The test consists of 20 items: two of which are forced-choice and the remaining are constructed-response format items.…”
Section: Instrumentsmentioning
confidence: 99%
“…If tests are understood to shape both the curriculum and teaching, an efficient way to improve the quality of education in critical thinking is developing the better tests (Yeh, 2001). Tiruneh et al (2016) stated that critical thinking tests which have been developed such as the Cornell Critical Thinking Test-Level Z (CCTT), the California Critical Thinking Skills Test (CCTST), the Ennis-Weir Critical Thinking Essay test, the Watson-Glaser Critical Thinking Appraisal, and the Halpern Critical Thinking Assessment (HCTA) were mostly general content-based and reviewed based on the following criteria: (a) is the test based on a clear DOI: 10.1021/xxx.xxxx.xxxxxx J.Sci. Learn.2017.1(1).…”
Section: Introductionmentioning
confidence: 99%